Avances para la evaluación del sello diferenciador en instituciones de educación superior - Farías Délano, Andrea Cristina (2016)
The present document gives an account of the validation process of the instrument "Self-evaluation of the Institutional Seal of the National School of Education of Cáritas Chile". This initiative is based on the need to have an instrument that will  provide information on the level at which the students of the Higher Technical Degree in Early Childhood Education, basic and first level, reached the competencies declared by the institution as centers of their training and differentiating the formation of similar institutions. It presents a proposal of self-evaluation with the objective of promoting the student's personal reflection on their strengths and aspects to be enhanced. As a result, a highly reliable instrument is obtained that allows comparative evaluations and valuable information for training processes.